Geometria dinâmica na sala de aula: o desenvolvimento do futuro professor de matemática diante da imprevisibilidade - Silva, Guilherme Henrique Gomes Da; Penteado, Miriam Godoy [UNESP] (Programa de Pós-Graduação em Educação para a Ciência, Universidade Estadual Paulista (Unesp), Faculdade de Ciências, campus de Bauru., 2013)
This paper presents the result of a research aiming to analyze how a study group, of prospective mathematics teachers, used dynamic geometry software in planning activities for a teaching practice. Before practicing with students, the group read and discussed papers from journals, explored Geogebra, dynamic geometry software, and planned a workshop to be held with students at high school level. A special highlight is given to the unpredictability which occurs in a ICT-based environment, and how this establishes a risk zone. Thus there are both technical and mathematical content related risks. The results show that a collective theoretical study was essential for the prospective teachers not to be paralyzed when facing unpredictability. Episodes are discussed illustrating how a risk zone can turn into a fruitful learning environment. The group provides conditions for reflecting and facing the unpredictability of a computer-based environment, stimulating professional development.

Este artigo é baseado em resultados de uma pesquisa cujo objetivo foi analisar como futuros professores de matemática, vinculados a um grupo de estudos, se apropriaram de um software de geometria dinâmica, de forma a inseri-lo em atividades de ensino. O grupo se reuniu para ler e discutir artigos científicos, explorar um software e elaborar uma oficina para alunos do Ensino Médio. Aqui são discutidas reflexões do grupo sobre os imprevistos que podem ocorrer quando o professor atua num ambiente de aprendizagem baseado em Tecnologia da Informação e Comunicação (TIC). São apresentados episódios que ilustram como uma zona de risco pode se constituir numa zona de possibilidades para aprendizagem da docência. O grupo fornece estímulo e condições para se refletir e enfrentar os imprevistos decorrentes de um ambiente computacional, o que impulsiona o movimento para o desenvolvimento profissional.
Dynamic geometry in the classroom: the development of prospective teachers in the face of unpredictability
Keywords: High school; Mathematics teaching; Dynamic geometry; Information technology and communication; ICT; Ensino Médio; Ensino de matemática; Geometria dinâmica; Tecnologia da informação e comunicação; TIC